ANALISIS STAKEHOLDERS (AKTOR KEBIJAKAN) DALAM PENGEMBANGAN OBYEK WISATA CANDI GEDONGSONGO DI KABUPATEN SEMARANG - Tsuraya Annisa Salsabila; R. Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Tourism development is an effort to create the synergy in the use of tourism resources as well as to increase the role of government and local people in Semarang Regency that has a lot of tourist attractions, one of the priorities is Gedongsongo Temple. The development of Gedongsongo Temple is done by several related stakeholders. Every stakeholder has different roles and tasks. The roles must correspond to every stakeholder’s scope so that the stakeholders analysis is being done in the process of the development; it is needed to prevent the overlapping and and to see the effectiveness of the stakeholders’ roles. By all means, the analysis connects each of the stakeholders who are involved on the development of Gedongsongo Temple. The connection produces a policy network. The result of the policy network helps every stakeholder to coordinate and to support one and another so that there will be no misconcepting and overlapping.